Urethral Interfractional Geometric and Dosimetric Variations of Prostate Cancer Patients: A Study Using an Onboard MRI - Pham, Jonathan; Savjani, Ricky R.; Yoon, Stephanie M.; Yang, Tiffany; Gao, Yu; Cao, Minsong; Hu, Peng; Sheng, Ke; Low, Daniel A.; Steinberg, Michael; Kishan, Amar U.; Yang, Yingli (Frontiers in Oncology, 2022)
Purpose: For a cohort of prostate cancer patients treated on an MR-guided radiotherapy (MRgRT) system, we retrospectively analyzed urethral inter-fraction geometric and dosimetric variations based on on-board MRIs acquired at different time points and evaluated on-board prostatic urethra visualization for urethra-focused online adaptive RT. Methods: 26 prostate cancer patients were prospectively scanned on a 0.35T MRgRT system using an optimized T2-weighted HASTE sequence at simulation and final fraction. Two radiation oncologists (RO1 and RO2) contoured the urethras on all HASTE images. The simulation and final fraction HASTE images were rigidly registered, and urethral inter-observer and inter-fractional geometric variation was evaluated using 95th percentile Hausdorff distance (HD95), mean-distance-to-agreement (MDA), center-of-mass shift (COMS), and DICE coefficient. For dosimetric analysis, simulation and final fraction HASTE images were registered to the 3D bSSFP planning MRI and 3D bSSFP final setup MRI respectively. Both ROs’ urethra contours were transferred from HASTE images for initial treatment plan optimization and final fraction dose estimation separately. Stereotactic body radiotherapy (SBRT) plans, 40Gy in 5 fractions, were optimized to meet clinical constraints, including urethral V42Gy≤ 0.03cc, on the planning MRI. The initial plan was then forward calculated on the final setup MRI to estimate urethral dose on the final fraction and evaluate urethral dosimetric impact due to anatomy change. Results: Average inter-observer HD95, MDA, COMS, and DICE were 2.85±1.34mm, 1.02±0.36mm, 3.16±1.61mm, and 0.58±0.15, respectively. Average inter-fraction HD95, MDA, COMS, and DICE were 3.26±1.54mm, 1.29±0.54mm, 3.34±2.01mm, and 0.49±0.18, respectively. All patient simulation MRgRT plans met all clinical constraints. For RO1 and RO2, 23/26 (88%) and 21/26 (81%) patients’ final fraction estimated urethral dose did not meet the planned constraint. The average urethral V42Gy change was 0.48±0.58cc. Conclusion: Urethral inter-fraction motion and anatomic change can result in daily treatment violating urethral constraints. On-board MRI with good visualization of the prostatic urethra can be a valuable tool to help better protect the urethra through patient setup or online adaptive RT.